State size as measured in terms of public spending and world health, 1990-2000 (2005)
ABSTRACT: Objective: To determine the relationship between state size (measured in terms of public spending) and public health indicators in a sample of countries representing all regions of the world and from 1990-2000. Methods: An ecological study was performed using data on Central Government Spending (CGS) and per capita Gross National Product (GNP) obtained from the International Monetary Fund, and on life expectancy, maternal, and infant mortality, provided by the World Health Organization. A multiple linear regression model was fitted to estimate the effect of CGS on health, which also took into consideration per capita GNP and geographical region. Results: CGS varied little over the study period, with convergence around an average of 28%, but within a relatively wide range (7.80-53.0%); the countries with the strongest economies (according to per capita GNP) had the highest levels of CGS. The influence of this factor was particularly relevant for the infant mortality rate (r = 0.40; beta = –1.327; EE = 0.237; t = –5.590; p < 0.001). Per capita GNP and geographic location were also associated with variations in health; health indicators tended to be worse for poorer countries in Africa and Asia. In the adjusted model, CGS was statistically significant with regard to infant and maternal mortality rates. Conclusion: The study suggests that state size (in terms of public spending) has an important influence upon health and particularly upon mortality. Although it is important to bear in mind the limitations of this study and the reduced time window used, these results should be taken into consideration in the current political and epidemiological debate.